2020
DOI: 10.1007/s42979-020-00279-9
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis on Urdu Tweets Using Markov Chains

Abstract: This paper presents a sentiment analysis approach based on Markov chains for predicting the sentiment of Urdu tweets. Sentiment analysis has been a focus of natural language processing (NLP) research community from the past few decades. The reason for this growing interest is twofold. First, the complexity involved in identifying sentiment from the unstructured text makes it a challenging problem for the research community. Second, sentiment analysis has a wide variety of applications ranging from industry to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Their experiments revealed that CNN with multiple filters (3,4,5) achieved the highest rank, while BilSTM outperformed LSTM and CLSTM. In [27], the authors used a single layer CNN with multiple filters for document-level text classification and found it superior to the baseline methods. Asim et al [29] assessed performance of state-of-the-art ML, DL, and hybrid model for document classification.…”
Section: Deep Learning Based Approachmentioning
confidence: 99%
“…Their experiments revealed that CNN with multiple filters (3,4,5) achieved the highest rank, while BilSTM outperformed LSTM and CLSTM. In [27], the authors used a single layer CNN with multiple filters for document-level text classification and found it superior to the baseline methods. Asim et al [29] assessed performance of state-of-the-art ML, DL, and hybrid model for document classification.…”
Section: Deep Learning Based Approachmentioning
confidence: 99%
“…In this section is a brief overview of the literature. For predicting the emotion of Urdu tweets, Zarmeen Nasim and Sayeed Ghani [1] suggested an emotion analysis approach according to the Markov chains. The recovery of valuable information from a vast volume of data is one of the fields of text mining.…”
Section: Related Workmentioning
confidence: 99%
“…Sentiment analysis has been an essential mechanism in practical life when provides peoples with others' opinions; in which this could be effective in others' decision making for example in selecting a movie to watch, or purchasing a product. 1,2 Many e-commerce and commercial websites (e.g., Amazon for online purchase of their goods), or YouTube (e.g., for online video sharing) or other social media platforms apply automated sentiment analysis methods to catch opinions of potential consumers or purchasers on their products and increase the consumer purchase decision. Hence, applying automated sentiment analysis is increasing between local stores and enterprises to maintain positive reviews of their services or products while their user data are exponentially generated.…”
Section: Introductionmentioning
confidence: 99%